Implementing the Family-Led Care model for preterm and low birth weight newborns in Malawi: Experience of healthcare workers - Patani Mhango; Effie Chipeta; Adamson S. Muula; Judith Robb-McCord; Patrice White; James A. Litch; Irene Kamanga; Rebecca Freeman; Anne-Marie Bergh (African Journal of Primary Health Care & Family Medicine, 2020)
Background: Every Preemie–SCALE developed and piloted the Family-Led Care model, an innovative, locally developed model of care for preterm and low birth weight babies receiving kangaroo mother care. Aim: The aim of this study was to describe healthcare workers’ experience using Family-Led Care. Setting: This study was conducted in five health facilities and their catchment areas in Balaka district, Malawi. Methods: The mixed-methods design, with two data collection periods, included record reviews, observations and questionnaires for facility staff and qualitative interviews with health workers of these facilities and their catchment areas. The total convenience sample comprised 123 health professionals, support staff and non-professional community health workers. Results: Facility-based staff generally had positive perceptions of Family-Led Care (83%). Knowledge and application-of-knowledge scores were 69% and 52%, respectively. A major change between the first and the second data periods was improvement in client record-keeping. Documentation of newborn vital signs increased from 62% to 92%. Themes emerging from the qualitative interview analysis were the following: benefits of Family-Led Care; activities supporting the implementation of Family-Led Care; own care practices; and families’ reaction to and experience of Family-Led Care. Conclusion: This article reports improved quality of care through better documentation and better follow-up of preterm and low birth weight babies receiving kangaroo mother care according to the Family-Led Care model. Overall, health workers were positive about their involvement, and they reported positive reactions from families. Lessons learned have been incorporated into a universal Family-Led Care package that is available for adaptation by other countries.